WAWA: Mobile educational tool for learning the Kichwa language for the communities of the Napo River in Loreto, Peru - Ocampo Yahuarcani, Isaac (2022)
This paper presents an experience related to the design, development and validation of the Wawa mobile application to be used as an educational tool for learning the Kichwa language for the communities of the Napo River in Loreto, Peru. For the validation we have resorted to the comparison of two learning methodologies, the traditional one and the experimental one in which the use of the mobile application is given. The results of the tests with school-age students have shown a superior effectiveness with the use of the application, compared to the traditional teaching method.